(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to investigate the hepatoprotective effect of the combination extract of Andrographis paniculata and Eclipta prostrata (XTL-CM extract) on a chronic ethanol-induced liver injury model in mice. Subjects and Methods: ICR mice were administered ethanol orally for 4 weeks with gradually increasing concentrations each week (10%, 20%, 30%, and 40% ethanol). The animals were then treated with the XTL-CM extract at doses of 0.504 g/kg and 1.08 g/kg in the treatment groups, and silymarin at a dose of 0.1 g/kg in the reference group, for five weeks. Subsequently, the mice were evaluated for biochemical parameters, including AST and ALT levels, as well as oxidative stress-related hepatoprotective effects on hepatic MDA and GSH content. Results: The combination extract from XTL-CM at doses of 0.504 g/kg and 1.08 g/kg significantly reduced serum AST levels (19.26% and 29.05%; respectively); ALT levels (24.53% and 23.70%; respectively) after 4 weeks; and hepatic MDA content (31.11% and 31.76%; respectively) after 5 weeks. Moreover, the extract increased hepatic GSH content (44.66% and 54.88%, respectively). These effects were comparable to those observed in the group treated with silymarin at 0.1 g/kg in the chronic ethanol-induced liver injury model. Conclusion: The combination extract of Andrographis paniculata and Eclipta prostrata demonstrated hepatoprotective activity against chronic ethanol-induced liver injury through antioxidant mechanisms, similar to the effect of silymarin at 0.1 g/kg.